ICD-9 Code-Based Venous Thromboembolism Performance Targets Fail to Measure Up. (September 2016) - Lau, Brandyn D.; Haut, Elliott R.; Hobson, Deborah B.; Kraus, Peggy S.; Maritim, Chepkorir; Austin, J. Matthew; Shermock, Kenneth M.; Maheshwari, Bhunesh; Allen, Paul X.; Almario, Aileen; Streiff, Michael B.
Venous thromboembolism (VTE) is a common complication among hospitalized patients. Suboptimal prevention practices have prompted payers to consider hospital-associated VTE as a potentially preventable condition for which financial incentives or penalties exist to drive practice improvement. The authors reviewed all cases of hospital-associated VTE at the Johns Hopkins Hospital between July 1, 2010, and June 30, 2011, that were identified by ICD-9 codes used by a state-run pay-for-performance quality improvement program. Of 157 patients identified as having developed hospital-associated, potentially preventable VTE, only 92 (58.6%) patients developed radiographically confirmed VTE that were potentially preventable. This misclassification of VTE overestimates the marginal additional treatment cost by more than 860 000 and amounts to nearly 200 000 in lost reward in one year alone. ICD-9 codes alone have extremely low positive predictive value to identify true VTE events. The authors recommend linking provision of risk-appropriate prophylaxis to VTE outcomes as a better target for performance improvement.